2019
DOI: 10.17583/mcs.2019.3809
|View full text |Cite
|
Sign up to set email alerts
|

La violencia Masculina en la Pareja como Proceso Relacional: Un Desafío de Superación Cultural

Abstract: The present essay tries to understand the dynamics of domestic violence from the three following angles: masculinity, identity and power relationships as socio-cultural expressions. The first two are approaches to masculinity as a culture construct, its relationship with the process of culture identities and the exercise of violence against the intimate partner as a mechanism of cohesion. The third angle is based upon Bourdieu’s (2000) concept of power and domination, in dialogue with Ramirez's explanatory pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
1
3
0
3
Order By: Relevance
“…This is in line with previous studies that pointed out this kind of criticism towards men with an oppressed masculinity but not towards men with violent features [35]. Related to the theory of micromachismo, the participants in this study explained how it implies that all men are the same, while the scientific literature has shown that this is not so [36,37].…”
Section: Discussionsupporting
confidence: 91%
“…This is in line with previous studies that pointed out this kind of criticism towards men with an oppressed masculinity but not towards men with violent features [35]. Related to the theory of micromachismo, the participants in this study explained how it implies that all men are the same, while the scientific literature has shown that this is not so [36,37].…”
Section: Discussionsupporting
confidence: 91%
“…Domestic violence cannot be seen from the point of view of only men or women because they both play a role. This is a consequence of globalization which results in new relations between men and women (Bustamante et al, 2019).…”
Section: Intellectual Dimensionmentioning
confidence: 99%
“…Hubungan realional yang baru ini tampak dari berkurangnya kekerasan dalam rumah tangga yang dilakukan oleh laki-laki (Bustamante et al, 2019). Bahkan, hal ini pulalah yang memunculkan paradigma baru tentang konsep maskulinitas yang melibatkan laki-laki dalam usaha memerangi kekerasan gender terhadap perempuan (Joanpere & Morlà, 2019).…”
Section: Pendahuluanunclassified
“…Globalisasi memang telah memberikan pengaruh terhadap konsep maskulinitas. Relasi baru antara lakilaki dan perempuan tercipta oleh adanya globalisasi ini (Bustamante et al, 2019). Munculnya fenomena feminitas secara tidak langsung pasti berimbas pada dinamika perubahan pada aspek maskulinitas.…”
Section: Ra Sah Dipikir Nduwe Bojo Sing Galak Urip Mung Sepisan Kudu Digawe Penak Kudu Kuwat Atine Wani Nanggung Bebane Kabeh Dilakoni Yeunclassified